Formulasi Masker Gel Peel Off dari Ekstrak Etanol Biji Kopi Robusta Hijau (Coffea canephora) dengan Alkohol Polivinil - Lydia Septa Desiyana; Meutia Faradilla; Arienovita Nurul Istiqomah (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Robusta green coffee beans (Coffea canephora) have strong potential to be used as antioxidants which can inhibit free radicals that causes premature aging. The peel-off gel mask is a cosmetic product that increases the penetration of active ingredients, is easy to use, and maintains the natural moisture of the skin. This research aimed to examine the possibility of the ethanolic extract of Robusta green coffee beans into a peel-off gel preparation. A peel-off gel mask made from the ethanolic extract of Robusta green coffee beans was formulated using 3 polyvinyl alcohol (PVA) concentrations to obtain the best preparation, which were 10% (F1), 12% (F2), and 14% (F3). All preparations produced a clear yellowish gel. Only F3 met the qualifications for all evaluation tests. The results of a mechanical property test showed that F3 has the best value for tensile strength and elongation. There were statistically significant differences between the results of the evaluation tests before and after the stability test. The results of irritation tests showed that none of the formulas caused irritation. The best peel off gel mask preparation made with ethanolic extract of Robusta green coffee beans was formula F3 that used 14% PVA.